2012
DOI: 10.1038/cdd.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ras/Mapk pathway signaling inhibits Myc-induced lymphomagenesis

Abstract: Although the Myc transcription factor has been shown necessary for the oncogenic function of Ras, the contribution of Ras pathway signaling to the oncogenic function of Myc remains unresolved. We report the novel findings that Myc alone induced Ras/Mapk pathway signaling, and increased signaling following growth factor stimulation. Deletion of the scaffold protein kinase suppressor of Ras 1 (Ksr1) attenuated signaling through the Ras/Mapk pathway, including activation following Myc induction. B cells that lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…154 More recently, it has been shown that the impairment of RAS-MAPK pathway in mice deficient for KSR1 gene (encoding a scaffold protein of MAPK) results in a decrease in Myc-induced lymphomagenesis in a murine model. 155 …”
Section: Mapk Inhibitorsmentioning
confidence: 99%
“…154 More recently, it has been shown that the impairment of RAS-MAPK pathway in mice deficient for KSR1 gene (encoding a scaffold protein of MAPK) results in a decrease in Myc-induced lymphomagenesis in a murine model. 155 …”
Section: Mapk Inhibitorsmentioning
confidence: 99%
“…20 Cell cycle analysis was determined by flow cytometry after staining with 50 μg/mL propidium iodide (Invitrogen). Cell proliferation rate was also determined, at the indicated times, by flow cytometry after staining with carboxyfluorescein succinimidyl ester (CFSE; Invitrogen).…”
Section: Cell Viability Proliferation and Cell Cycle Assaysmentioning
confidence: 99%
“…16,17 Additionally the B-cell receptor, by stabilizing the amount and activity of the oncoprotein c-Myc, 18,19 might facilitate B-cell lymphomagenesis through the CD19/RAS/ERK pathway, which can promote the expression of anti-apoptotic proteins. 19,20 Indeed, previous experimental data acquired through the use of Eμ-Myc transgenic mice demonstrated that the c-Myc/ERK/CD19 feedback signaling loop is important for the malignant transformation of B cells and in determining the severity of lymphomas. 19,20 Chromosomal overexpression of translocation-elicited c-Myc induces the transcription of cyclin and cyclin-dependent kinase (CDK) genes which also relies significantly on CD19/ERK cascade-mediated phosphorylation of c-Myc on Ser62.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations